التضخم في الاقتصاد السوري خلال المدة (2001 – 2010) - صندوق, عفيف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
التضخم مرض اقتصادي يعيق النمو, ويبدد جهود التنمية الاقتصادية. على الرغم من السياسات الاقتصادية التي سارت عليها الحكومات السورية المتعاقبة, والتي من خلالها استطاعت إلى حد كبير أن تحقق استقراراً نسبياً مقبولاً في المستوى العام للأسعار, وسعر الصرف؛ فإنه يمكننا أن نلحظ عوامل عدة تضغط على ارتفاع الأسعار خلال مدة الدراسة. ويمكن للاقتصاد السوري التخفيف من ضغوط عوامل ارتفاع الأسعار من خلال متابعة تطبيق حزمة متكاملة من الإصلاحات الاقتصادية. Inflation is an economic illness which restrains development and wastes economic development efforts. In spite of the economic policies used by consecutive Syrian governments which were able to achieve relatively acceptable constancy of general level of prices and exchange rates, we can notice some factors which exert pressure on prices increasing during the period of this study. In fact, Syrian economy can reduce the pressing factors of price rise by resuming the application of an integrated package of economic reform.